Unraveling the Process of Knowledge Integration in Agile Product Development Teams - Julia Haselsteiner (Junior Management Science (JUMS), 2022)
Agile product development seems to be the solution for many companies to drive innovation and shorten time-to-market, but what mechanisms lie behind the promises of faster development times and more innovative products? Defined as locus of innovation and driver of dynamic performance, the concept of cross-functional knowledge integration and the organizational learning literature have the potential to provide answers here. Recent empirical studies imply that knowledge integration happens on multiple levels that influence each other, and that environmental uncertainty leads to changes in the knowledge integration process. However, the interplay of individual-level and group-level knowledge integration has not yet received adequate attention and prior studies do not show how knowledge integration changes over shorter periods of time. This paper takes a grounded theory approach to explore the knowledge integrating mechanisms in two agile product development teams. The resulting iterative process model shows how agile teams integrate diverse contributions of individual team members into a new product, how internal and external factors trigger alterations in knowledge integration practices, and how agile teams adapt to changes in coordination and collaboration demands.
Keywords: 650; Agile product development; knowledge integration; cross-functional teams; organizational learning